PENGARUH FASILITAS DAN KUALITAS PELAYANAN PRAMUSAJI TERHADAP KEPUASAN PELANGGAN DI THE PATIO RESTAURANT NATRA BINTAN - Hetty Yulianti Sihite; Nurul Fitri Handayani (Bogor Hospitality Journal, 2023)
This research aims to examine the effect of This research aims to examine the effect of facilities and waiter service quality on customer satisfaction at The Patio Restaurant Natra Bintan. This research uses primary data sources. By conducting observations and distributing questionnaires to 100 respondents, where the respondents were guests who had used restaurant facilities and experienced waiter service at The Patio Restaurant Natra Bintan. The facility variable (X1) is measured using 10 question indicators or statements and the waiter service quality variable (X2) is measured using 9 question or statement indicators. For the customer satisfaction variable (Y), there are 10 indicator questions or statements. The analysis techniques in this research are validity test, reliability test, multiple linear regression analysis, coefficient of determination analysis, and t test (partial). This research methodology uses a descriptive quantitative approach. The statement from the t test (partial) is that if the P-value Xn < alpha (0.05) then it can be said that there is a significant influence. The results of the facility variable have a positive and significant effect on customer satisfaction as shown by a value of 0.016 < 0.05. Then, the waiter service quality variable has a positive and significant effect on customer satisfaction as indicated by a value of 0.00 < 0.05. Keywords : Customer Satisfaction, Facilities, Waiter Service Quality